Smart cities and urban áreas: aquaponics as innovative urban agriculture - Dos Santos, Maria José Palma Lampreia (2018)
Aquaponics is an innovative smart and sustainable production system for integrating aquaculture withhydroponic vegetable crops, that can play a crucial role in the future of environmental and socio-economicsustainability in smart cities. These cities aim mobilize all knowledge centers and Information and Com-munication Technologies (ICT) into innovation hubs in order to strengthen the socio-economic progress.Nowadays the production, transport and logistics of food requires high costs and transport and harvestfrom other parts of the planet to the cities, associated to intensive polluting technologies. Aquaponics canplay a key role enabling local production, fresh, free of pesticides and healthy with short supply chainsin the cities.Despite the technical developments in aquaponics there is still no integrated approach to analyzetheir potential as urban agriculture. This paper aims to contextualize the aquaponics as urban farmingand analyze the necessary developments in that field, namely, the need of an integrated approach fromproducers to consumers on smart cities.So, this paper analyzes the importance of Theory of Planned Behavior on aquaponics stakeholder’s deci-sion making process and the efficiency analysis in aquaponics systems by parametric (Data EnvelopmentAnalysis), and non-parametric methods (stochastic frontier production) as an integrated and innovativeapproach.